Pengaruh Rasio kecukupan Modal, Beban Operasional dan Pendapatan Operasional, Dan Tingkat Risiko Pembiayaan Terhadap Profitabilitas (ROA) Pada PT Bank Muamalat Indonesia Periode 2015-2020 - Betha Retno Hermawati; Dedi Suselo (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This study aims to examine the effect of the Capital Adequacy Ratio, Operating Expenses and Operating Income, and the Level of Financing Risk on Profitability (ROA) at PT Bank Muamalat Indonesia for the 2015-2020 period. The method used is a quantitative method using secondary data. The data used in this study are the quarterly financial statements of PT Bank Muamalat Indonesia for the 2015-2020 period. The statistical test used is the classical assumption test and multiple linear regression analysis. The result of the coefficient of determination (R2) is 0.833 or 83.3%. This value can be interpreted that the Capital Adequacy Ratio (CAR), BOPO, and Financing Risk Level (NPF) have a significant effect on profitability by 83.3%, and 16.7% is explained by other variables outside the research model. Partially, the BOPO variable has a significant effect on profitability. Meanwhile, the Capital Adequacy Ratio (CAR), and Financing Risk Level (NPF) have no significant effect on profitability. Simultaneously, the Capital Adequacy Ratio (CAR), BOPO, and Financing Risk Level (NPF) have a significant effect on profitability.